Psychometric evaluation of a new instrument to hookah tobacco smoking-related factors in the Iranian female university students based on the Extended Parallel Process Model - Fereshteh Zamani-Alavijeh; Zahra Heidari; Firoozeh Mostafavi; Saeed Bashirian; Zeinab Makvandi; Roya Kelishadi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The higher prevalence of hookah tobacco smoking (HTS) has become worrisome in women. Thus, it is essential to identify and measure the perceptions associated with this unhealthy behavior as well as the type of response to risk messages to design the effective programs. This study aimed to psychometric evaluation of a new instrument, named the Extended Parallel Process Model-Hookah Tobacco Smoking Questionnaire (EPPM-HTSQ), for female university students. MATERIAL AND METHODS: This methodological study was conducted in 2019-2020 in central and western Iran. The first version of the instrument was developed with 97 items. Face, Content, and construct validity methods were used to assess the EPPM-HTSQ validity. The data viability for factorability was guided through Kaiser-Meyer-Olkin (KMO) measure of sample adequacy (Values >0.7) and Bartlett's test of Sphericity (P < 0.05). The Exploratory Factor Analysis (EFA) method with varimax rotation and SPSS software was performed to identify the main factors of the questionnaire and interpretable factors. The internal consistency and external reliability were determined. The test-retest was used for evaluating the stability of tools. RESULTS: During the assessment of the face and content validity 71 items remained in the questionnaire. EFA led to the extraction of nine dimensions: "Focusing on superior rewards," "Response Efficacy," "Perceived physical threat," "Perceived social threat," "Self-efficacy," "Fear control," "Attitude," "Fear," and "Intention" Kaiser-Meyer-Olkin (KMO) test (0.957) and Bartlett's test (P < 0.001). Cronbach's alpha (0.871-0.951) and ICC (0.985-0.998) were approved for scale dimensions. CONCLUSION: Important findings of the present study were the development and validation of the EPPM-HTSQ for measuring EPPM variables in relation to HTS; introducing a new variable "focusing on superior rewards"; as well as, the new classification of the concept of "perceived threat." The final version of the EPPM-HTSQ is a valid and reliable tool, but it is suggested to be re-evaluated in other studies with different populations and sample sizes.